SOCIETY AND KNOWLEDGE - Childe, V. Gordon (Vere Gordon), 1892-1957. ([S.l.])
1 online resource.
Keywords: Originally published in 1956, the well-known archaeologist here takes on the role of philosopher. The author argues that knowledge is a social phenomenon, and that our intellectual life is the product of social heritage: reality is the product of different opinions of various societies.